Experimental study and in-situ FBG monitoring of process-induced strains during autoclave co-curing, co-bonding and secondary bonding of composite laminates. (March 2021) - Moretti, L.; Olivier, P.; Castanié, B.; Bernhart, G.
Abstract: The geometric stability of bonded structural parts, such as self-stiffened panels, is a critical issue in aeronautics. However, autoclave curing and bonding of large complex integrated primary structures often induce distortions compromising their geometric stability. Composite cure-induced strains and distortions have been extensively studied in the literature but the influence of the adhesive on these distortions has often been overlooked. More experimental data are therefore necessary to properly understand its influence on process-induced strains and its behaviour during cure. The present paper reports a wide range of new experimental investigations showing the non-negligible influence of the adhesive on cure-induced distortions of composite assemblies. The experimental data presented include post-cure distortion measurements, optical microscope imaging, micro-tomography imaging and FBG in-situ strain monitoring during an autoclave bonding process. These experiments demonstrate the impact of the adhesive film behaviour and of the manufacturing bonding process on final distortions and strains of composite assemblies.